Dual-Tracer PET/CT Differentiates 2 Types of Primary Cancers and Metastases in a Patient With Crossed Fused Renal Ectopia. (February 2019) - Ho, Chi-lai; Chen, Sirong; Leung, Yim Lung; Cheng, Kam Chau; Wong, Yuet Hung
Abstract : Abstract: A patient was found incidentally on dual-tracer ( 11 C-acetate [ACT] and 18 F-FDG [FDG]) PET/CT for having crossed fused renal ectopia and 2 types of malignant tumors, colonic carcinoma and renal cell carcinoma (RCC), each having its own characteristic tracer avidity. Multiple liver metastases were also mutually exclusive, with a purely ACT-avid group of metastatic lesions from RCC and another FDG-avid group from colonic carcinoma. Bone and lung metastases, however, could not be readily distinguishable in terms of primary origins. Crossed fused renal ectopia is a rare anomaly, even rarer to have RCC coexisting with a second primary malignancy.